Comprehensive Genomic Profiling of Rare Tumors in China: Routes to Immunotherapy - Wang, Shuhang; Fang, Yuan; Jiang, Ning; Xing, Shujun; Li, Qin; Chen, Rongrong; Yi, Xin; Zhang, Zhiqian; Li, Ning (Frontiers in Immunology, 2021)
Comprehensive Genomic Profiling may be informative for novel treatment strategies and to improve outcomes for patients with rare tumours. This study aims to discover opportunities for use of immune checkpoint inhibitors (ICIs) treatments, which have already been approved for routine use in common tumour types, in patients with rare tumours. We collected immunotherapy-related indicators data from a total of 852 rare tumour patients from across China, including 136 programmed cell death ligand-1 (PD-L1) expression, 821 tumours mutational burden (TMB), 705 microsatellite instability (MSI) and 355 human leukocyte antigen class I (HLA-I) heterozygosity reports. We calculated the positive rates of these indicators and analysed the consistency relationship between TMB and PD-L1, TMB and MSI, and HLA-I and PD-L1. The prevalence of PD-L1 positive, TMB-H, MSI-H and HLA-I -heterozygous was 47.8%, 15.5%, 7.4% and 78.9%, respectively. The consistency ratio of TMB and PD-L1, TMB and MSI, and HLA-I and PD-L1 was 54.8% (78/135), 87.3% (598/685) and 47.4% (54/114), respectively. The prevalence of the four indicators varied widely across tumours systems and subtypes. The probability that neuroendocrine tumours (NETs) and biliary tumours may benefit from immunotherapy is high, since the proportion of TMB-H is as high as 50% and 25.4% respectively. The rates of PD-L1 positivity, TMB-H and MSI-H in carcinoma of unknown primary (CUP) were relatively high, while the rates of TMB-H and MSI-H in soft tissue tumours were both relatively low. Our study revealed the distribution of immunotherapeutic indicators in patients with rare tumours in China. Comprehensive genomic profiling may offer novel treatment paradigms to address the limited options for patients with rare tumours.